Developing and Adapting Business Models in Technology-Based Startups - Shankar, Vidya Shankar (Journal of Advanced Research in Technological Entrepreneurship and Start-Up Incubation Ecosystems, 2025)
The business model is a fundamental framework that defines how a technology-based startup creates, delivers, and captures value in a competitive marketplace. In the rapidly evolving tech industry, where disruption is constant, developing and adapting an effective business model is crucial to ensuring the long-term sustainability, scalability, and market leadership of a startup. This review article provides an in-depth examination of the core principles, strategies, and frameworks for developing and adapting business models within technology startups. The paper highlights the essential role of market understanding, innovation, and flexibility in the crafting of business models that are resilient to external changes and adaptable to emerging trends. It discusses how technology ventures can respond to challenges such as technological disruptions, fluctuating consumer preferences, regulatory shifts, and intense competition. Furthermore, this review offers actionable insights into how startups can implement successful strategies for business model innovation, adaptation, and evolution to stay relevant in dynamic markets. The review also explores popular business model frameworks, including the Business Model Canvas, Lean Startup methodology, and value proposition design, providing practical advice on their application in real-world scenarios. In conclusion, understanding and continuously adapting business models are critical for the success of technology-based startups, as it directly influences their ability to capture new market opportunities, sustain growth, and maintain a competitive advantage over time.